The Use of Arabic with a Communicative Approach: - Mardhiyah M; Muhamad Jaeni; Siti Salamah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to explore a sociolinguistic review of the use of Arabic with a communicative approach in Klego Village, East Pekalongan District, Pekalongan City. This research is a library research and is descriptive-analytic in nature whose data is taken from the results of excavation and searching of books and other references relevant to the research theme. then the data were analyzed by deductive and comparative methods. The results of the study indicate that the communicative approach in using Arabic is an approach that aims to develop communicative abilities and teaching procedures for the four language skills, namely listening, speaking, reading, and writing in a balanced way. The use of language skills with a communicative approach in terms of sociolinguistics contains the same content, namely the practical purpose of using language which is then applied in the real life of society. One of the non-linguistic factors that can affect the teaching of Arabic from a social context is a social phenomenon. While the social context itself is divided into several things, namely: home (residence), community (surrounding environment), schools, social gatherings and groups, mosque groups, play groups, and mass media. Keywords: Sociolinguistics, Arabic language teaching, communicative approach.